2015
DOI: 10.1002/jsfa.7387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cu/Zn-SOD enzyme activities and gene expression in soybean under low nitrogen stress

Abstract: GmCZ-SOD is important for adaptability of soybean to nitrogen limitation and these results provide useful information to unravel its biological role in low nitrogen resistance in plants. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In soybean, ten SOD isoenzymes were identified in different tissues (Wang et al, 2016). For example, one MnSOD isoenzyme was mainly detected in stems and seeds.…”
Section: Identification and Phylogenetic Analysis Of Sod Genes In Soymentioning
confidence: 99%
See 1 more Smart Citation
“…In soybean, ten SOD isoenzymes were identified in different tissues (Wang et al, 2016). For example, one MnSOD isoenzyme was mainly detected in stems and seeds.…”
Section: Identification and Phylogenetic Analysis Of Sod Genes In Soymentioning
confidence: 99%
“…The photosynthetic rate, sugar production, N metabolism and amino acid production were also significantly inhibited under alkaline stress (at high pH) (Hu et al, 2015). Further, alkaline stress has affected 434 million ha of land and limited the crop productivity worldwide (Chen et al, 2018), although single form of soybean SOD gene has been identified under various stresses (Gopavajhula et al, 2013;Wang et al, 2016). It is necessary to explore the roles of soybean SOD family under environmental stresses, especially under alkaline stress.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we observed that down-regulated gma-miR398c displayed the function of a major gene that negatively regulated the expression of multiple peroxisome-related genes (e.g., GmCSD1a/b, GmCSD2a, and GmCCS) ( Figure 2B). The enzymes encoded by these target genes represent the first protective barrier that efficiently eliminates free radicals and prevents plants from accumulating ROS to toxic [38] reported that GmCZ-SOD1 (Glyma05g04170) may be important in the adaptive evolution of nitrogen limitation in soybean, whereas it was identified as GmCCS (Glyma.05g055000) encoding a copper chaperone for superoxide dismutase in phylogenetic analysis ( Figure S5A). We determined that GmCCS is expressed predominantly in chloroplasts (Figure 4), similar to homologous genes in Arabidopsis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Many countries in the world, such as China, are facing the problems of excessive nitrogen application and low nitrogen utilization e ciency in winter wheat production [1]. Excessive application of nitrogen fertilizer is the main reason for the low nitrogen utilization e ciency in wheat [2]. At the same time, it causes environmental pollution and becomes a threat of the sustainable development of agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulated expression of alternative oxidase (AOX) consumes excess sugars, and then the induced AOX balanced the carbon and nitrogen under nitrogen de ciency [12][13][14]. GmCZ-SOD1 gene was highly induced in soybean root under nitrogen de ciency [2]. The transcriptome showed 1799 maize differentially expressed genes (DEGs) involving multiple pathways under nitrogen de ciency [11].…”
Section: Introductionmentioning
confidence: 99%